PENGARUH PAJAK INDUSTRI PARIWISATA DAN RETRIBUSI OBYEK WISATA TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI 12 KABUPATEN/KOTA PROVINSI RIAU TAHUN 2009−2013 - Cahyadi, Robi; Rasuli, Muhammad; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
One of indicators used to determine the effect of tourism on local revenue is through the development of tourism revenue received by the tax tourism indutry and tourism levy. Where this would describe the situation every tourism trip would be beneficial to the economy of a region that is in visited and impacted to the revenue which would increase also. This study aims to determine the tax effects of the tourism industry and tourism levy on revenue (PAD) in 12 districts / cities of Riau Province in 2009-2013. In this research used period (time series) data and latitude series data (cross section) while the source data using secondary data, then analyzed by the method of multiple linear regression (with SPSS version 16.0). The results of tests showed that the tax variable tourism industry and tourism levy variables have a significant effect on the variable revenue. T-test showed that the tourism industry tax variables have the most significant effect on the regional income variable t of 1.801 and significance probability of 0.005 <0.05. The magnitude of the effect that (R2) by these two variables together against the dependent variable that is equal to 24.7% while the remaining 75.3% is influenced by other variables not examined in this study.Keywords: tax tourism industry, tourism levy, local revenue